Sodium-ion structural battery and preparation process thereof

CN116565329BActive Publication Date: 2026-10-23CIVIL AVIATION UNIV OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310320351.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2026-10-23
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

[0005]但是,由于钠离子的半径大于锂离子的半径,现有的电极材料对于钠离子的脱嵌及电解质材料对于钠离子的快速传递难以有良好效率,且钠离子电池的能量密度低于锂离子电池,循环寿命也低于锂离子电池,并且受钠离子电池的质量影响,会给结构增加额外载荷,导致结构承载力下降

Benefits of technology

[0017]与现有技术相比,本发明所达到的有益效果是:本发明所设计的钠离子结构电池不仅可以承担机械载荷,保证原结构的强度,而且还能进行能量存储,实现了一种结构多种功能的优化,在新能源存储领域将有较大应用价值;并且本电池快充性能优异、安全性好,还对碳材料进行了改良处理,能够更好地承载钠离子,加强了传递效率;此外,使用3D打印技术可以节约材料和时间,打印出的产品具有很高的精度和复杂度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116565329B_ABST
    Figure CN116565329B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of carbon fiber energy storage composite materials and sodium ion battery design and preparation, and relates to a sodium ion structure battery and a preparation process thereof, which comprises carbon fiber filaments, an SPE coating, conductive materials, positive active particles, a PLA matrix and a current collector plate, wherein the current collector plate is provided with a composite material formed by mixing multiple layers of conductive materials, positive active particles and the PLA matrix, multiple carbon fiber filaments are spirally arranged to form a carbon fiber bundle, and the carbon fiber bundle is arranged in the composite material formed by mixing the conductive materials, the positive active particles and the PLA matrix, and the SPE coating is coated on the outer surface of the carbon fiber filaments. The sodium ion structure battery can not only bear mechanical load and ensure the strength of the original structure, but also store energy; the sodium ion structure battery has excellent fast charging performance and high sodium ion transfer efficiency; and the use of 3D printing technology can save materials and time, and has high precision and complexity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon fiber energy storage composite materials and sodium-ion battery design and preparation technology, and specifically relates to a sodium-ion structure battery and its preparation process. Background Technology

[0002] Electrochemical energy storage has become a major focus of energy storage system development due to its high flexibility and low geographical requirements.

[0003] Lithium-ion batteries are characterized by high operating voltage, high energy density, wide operating temperature range, long cycle life, no memory effect, and environmental friendliness. They are widely used in power battery fields such as automobiles and electric bicycles, energy storage fields such as power grids, industrial energy storage, home energy storage and communication energy storage, and 3C digital fields such as smartphones, laptops, smart wearable devices, and power banks.

[0004] While lithium-ion batteries are being used extensively, lithium salts are becoming a scarce resource globally. Scientists have turned their attention to sodium, which has properties similar to lithium. Sodium-ion batteries are cheaper, safer, perform better at low temperatures, and have better fast-charging capabilities, making them primarily used in energy storage and electric two-wheeler markets.

[0005] However, since the radius of sodium ions is larger than that of lithium ions, existing electrode materials are not efficient in the intercalation and deintercalation of sodium ions and in the rapid transfer of sodium ions by electrolyte materials. Furthermore, sodium-ion batteries have lower energy density and cycle life than lithium-ion batteries. Moreover, the mass of sodium-ion batteries can increase the load on the structure, leading to a decrease in the structural load-bearing capacity.

[0006] Currently, most emerging research focuses on laminated battery structures. The fabrication process of traditional laminated battery structures is relatively simple, but the interface of composite materials is weak, and the mechanical properties of polymer electrolyte matrix and cathode material are poor, which greatly limits the mechanical properties of traditional laminated battery structures. Summary of the Invention

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention relates to a sodium-ion battery and its fabrication process, comprising carbon fiber filaments, an SPE coating, conductive materials, positive electrode active particles, a PLA matrix, and a current collector. The current collector is provided with a composite material composed of a mixture of multiple conductive materials, positive electrode active particles, and a PLA matrix. Multiple carbon fiber filaments are spirally arranged to form a carbon fiber bundle, which is disposed in the composite material composed of the conductive materials, positive electrode active particles, and PLA matrix. The SPE coating covers the outer surface of the carbon fiber filaments.

[0008] Preferably, the SPE coating is a polymer PEGDA / NaClO4 / SCN / Na3Zr2Si2PO synthesized by ultraviolet light curing. 12 The composite electrolyte membrane has a white and opaque SPE coating.

[0009] Preferably, the mixing ratio of the conductive material to the positive electrode active particles is 4:1.

[0010] Preferably, the conductive material is Prussian blue Na2MnFe(CN)6.

[0011] Preferably, the positive electrode active particles are graphene particles.

[0012] Preferably, the current collector is an aluminum current collector.

[0013] A fabrication process for a sodium-ion battery includes the following steps: S1. Processing of carbon materials: Ferric citrate and ammonium chloride are mixed and ground evenly. The resulting mixture is carbonized at high temperature in a tube furnace filled with ammonia gas. The temperature is raised from room temperature to the set temperature. The resulting black powder is washed with 1M hydrochloric acid solution and deionized water, and then vacuum dried to obtain carbon materials. Finally, the prepared carbon materials, acetylene black and polytetrafluoroethylene are thoroughly mixed evenly to form a slurry. The material is pressed into filaments under a pressure of 15 MPa to form carbon fiber filaments, and then dried for later use. S2. Obtain carbon fiber bundles coated with SPE: Na3Zr2Si2PO 12 The powder was continuously ball-milled for 48 hours to reduce and homogenize the particle size, so that the particle size was in the range of 50-200 nm. The ball-milled Na3Zr2Si2PO4... 12 The powder was dispersed in an isopropanol solution and further sonicated for 1–2 hours to decompose the agglomeration of nanoparticles. After preparing the PEGDA-NaClO4-SCN mixture, a specified percentage of Na3Zr2Si2PO4 was added. 12 A certain amount of Na3Zr2Si2PO was dispersed. 12 Powder, PEGDA-NaClO4-SCN-Na3Zr2Si2PO 12 The mixture was continuously stirred for 18 hours to form a uniform slurry. Then, 1% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added. The viscous slurry was then cast into a Teflon box in the order of slurry-carbon fiber filaments obtained in step S1-slurry and cured under ultraviolet light for 1 hour to obtain carbon fiber filaments coated with SPE. Multiple carbon fiber filaments coated with SPE were spirally wound to obtain carbon fiber bundles coated with SPE. S3. Printing an integrated 3D sodium-ion battery structure: Using a five-axis 3D printer, the particles after mixing conductive materials, positive electrode active particles and PLA matrix are melted by a heater to obtain a hot melt. Then, the hot melt and the carbon fiber tow coated with SPE obtained in step S2 are co-extruded through an extrusion nozzle and printed layer by layer on a printing bed at ambient temperature and pressure to obtain a 3D sodium-ion battery structure.

[0014] S4. Assemble the complete sodium-ion battery structure: Connect the 3D sodium-ion battery structure printed in step S3 to the aluminum current collector to realize the complete sodium-ion battery structure.

[0015] Preferably, in step S1, the temperature is set to 700℃ and the heating rate is 5℃ / min, and the mass ratio of ammonium chloride to ferric citrate in step S1 is 1:1.

[0016] Preferably, the mass ratio of carbon material, acetylene black and polytetrafluoroethylene in the slurry of step S1 is 8:1:1.

[0017] Compared with existing technologies, the beneficial effects achieved by this invention are as follows: The sodium-ion structure battery designed in this invention can not only bear mechanical loads and ensure the strength of the original structure, but also store energy, achieving optimization of multiple functions in one structure, which will have great application value in the field of new energy storage; in addition, this battery has excellent fast charging performance and good safety, and the carbon material has been improved to better carry sodium ions and enhance the transfer efficiency; furthermore, the use of 3D printing technology can save materials and time, and the printed products have high precision and complexity. Attached Figure Description

[0018] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the structure of the present invention; In the diagram: 1. Carbon fiber filament; 2. SPE coating; 3. Conductive material; 4. Positive electrode active particles; 5. PLA matrix; 6. Current collector. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] like Figure 1As shown, a sodium-ion battery and its fabrication process include carbon fiber filaments 1, an SPE coating 2, a conductive material 3, positive electrode active particles 4, a PLA matrix 5, and a current collector 6. The current collector 6 is an aluminum current collector, and a composite material composed of multiple layers of conductive material 3, positive electrode active particles 4, and PLA matrix 5 is disposed on the current collector 6. The mixing ratio of conductive material 3 to positive electrode active particles 4 is 4:1. The conductive material 3 is Prussian blue Na₂MnFe(CN). 6, Furthermore, the positive electrode active particle 4 is a graphene particle, and multiple carbon fiber filaments 1 are spirally arranged to form a carbon fiber bundle. The carbon fiber bundle is disposed in a composite material composed of conductive material 3, positive electrode active particle 4, and PLA matrix 5. An SPE coating 2 is coated on the outer surface of the carbon fiber filaments 1. The SPE coating 2 is a polymer synthesized by ultraviolet light curing, namely PEGDA / NaClO4 / SCN / Na3Zr2Si2PO4. 12 The composite electrolyte membrane has a white and opaque SPE coating 2, which is a solid polymer electrolyte coating and a PLA matrix 5, which is a polylactic acid matrix.

[0021] A fabrication process for a sodium-ion battery includes the following steps: S1. Processing of carbon materials: Ferric citrate and ammonium chloride are mixed and ground evenly, with a mass ratio of ammonium chloride to ferric citrate of 1:1. The resulting mixture is carbonized at high temperature in a tube furnace filled with ammonia gas, from room temperature to a set temperature of 700℃ at a heating rate of 5℃ / min. The resulting black powder is washed with 1M hydrochloric acid solution and deionized water, and then vacuum dried to obtain carbon materials, acetylene black, and polytetrafluoroethylene. Finally, the prepared carbon materials, acetylene black, and polytetrafluoroethylene are thoroughly mixed evenly to form a slurry, with a mass ratio of carbon materials, acetylene black, and polytetrafluoroethylene of 8:1:1. The material is pressed into filaments under a pressure of 15 MPa to form carbon fiber filament 1, which is then dried for later use. For carbon materials, the doping of different heteroatoms is a crucial factor affecting electrochemical performance. In battery design, heteroatoms can donate a pair of electrons, altering the electron donor-acceptor properties of carbon materials. Simultaneously, heteroatom-modified carbon materials exhibit better wettability, facilitating contact between electrode materials and electrolytes. In redox reactions, doping carbon materials with non-metallic elements serves two main purposes: first, it breaks the electroneutrality of sp2 carbon, creating charge sites for oxygen molecule adsorption; second, it effectively utilizes the π electrons in carbon materials for oxygen molecule reduction. Furthermore, loading metals (Fe, Co, etc.) onto carbon materials can significantly enhance the activity of electrocatalysts. S2. Obtain carbon fiber bundles coated with SPE coating 2: Na3Zr2Si2PO 12The powder was continuously ball-milled for 48 hours to reduce and homogenize the particle size, so that the particle size was in the range of 50-200 nm. The ball-milled Na3Zr2Si2PO4... 12 The powder was dispersed in an isopropanol solution and further sonicated for 1–2 hours to decompose the agglomeration of nanoparticles. After preparing the PEGDA-NaClO4-SCN mixture, a specified percentage of Na3Zr2Si2PO4 was added. 12 A certain amount of Na3Zr2Si2PO was dispersed. 12 Powder, PEGDA-NaClO4-SCN-Na3Zr2Si2PO 12 The mixture is continuously stirred for 18 hours to form a uniform slurry. Then, 1% of 2-hydroxy-2-methyl-1-phenyl-1-propanone is added. The viscous slurry is then cast into a Teflon box in the order of slurry-carbon fiber filament 1 obtained in step S1-slurry. The mixture is cured under ultraviolet light for 1 hour to obtain carbon fiber filament 1 coated with SPE coating 2. Multiple carbon fiber filament 1 coated with SPE coating 2 are spirally wound to obtain carbon fiber bundle coated with SPE coating 2. To obtain SPE coating 2, solid phase extraction coating is polymerized from solution, leaving grafted polymer on each carbon fiber, and then polarization is performed at different times to obtain SPE coating 2 of different thicknesses. S3. Printing an integrated 3D sodium-ion battery structure: Using a five-axis 3D printer, the particles of conductive material 3, positive electrode active particles 4 and PLA matrix 5 are mixed and melted by a heater to obtain a hot melt. Then, the hot melt and the carbon fiber tow coated with SPE coating 2 obtained in step S2 are co-extruded through an extrusion nozzle and printed layer by layer on a printing bed at room temperature and pressure to obtain a 3D sodium-ion battery structure.

[0022] S4. Assemble the complete sodium-ion battery structure: Connect the 3D sodium-ion battery structure printed in step S3 to the aluminum current collector 6 to realize the complete sodium-ion battery structure.

[0023] For the fabrication of battery structures in structured batteries, a co-extrusion deposition method is used to additively manufacture battery structures: a carbon fiber 3D printer is required, whose movement is controlled by a multi-axis 3D printer, thus allowing toolpaths to be drawn in three-dimensional space; for a given composition, particle-based extrusion processes generally exhibit better printability, which otherwise leads to clogged or brittle filaments, while fusion-based filament manufacturing processes result in filaments that are too brittle to handle. To maximize energy capacity, the ratio of positive electrode active particles 4 to conductive material 3, namely Prussian blue Na2MnFe(CN)6, was first optimized to achieve the highest ionic conductivity. With a fixed percentage of PLA binder, a 1:4 ratio of positive electrode active particles 4 to conductive material 3 produced the highest ionic conductivity.

[0024] By combining the excellent mechanical load-bearing capacity, electrical conductivity, and good sodium ion transfer efficiency of carbon fiber composite materials, a carbon fiber structure battery that can be 3D printed was designed to achieve integrated mechanical load-bearing and energy storage. While reducing the structural weight, it can also provide energy storage function, which will have great application value in the field of new energy storage.

[0025] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A sodium-ion battery, comprising carbon fiber filaments (1), an SPE coating (2), a conductive material (3), positive electrode active particles (4), a PLA substrate (5), and a current collector (6), characterized in that: The current collector (6) is provided with a composite material made of a mixture of multilayer conductive material (3), positive electrode active particles (4) and PLA matrix (5). Multiple carbon fiber filaments (1) are spirally arranged to form a carbon fiber bundle, and the carbon fiber bundle is disposed in the composite material made of the mixture of conductive material (3), positive electrode active particles (4) and PLA matrix (5). The SPE coating (2) is coated on the outer surface of the carbon fiber filaments (1). The current collector (6) is an aluminum current collector. The sodium-ion battery fabrication process includes the following steps: S1. Processing of carbon materials: Iron citrate and ammonium chloride are mixed and ground evenly. The resulting mixture is carbonized at high temperature in a tube furnace filled with ammonia gas. The temperature is raised from room temperature to the set temperature. The resulting black powder is washed with 1M hydrochloric acid solution and deionized water, and then vacuum dried to obtain carbon materials. Finally, the prepared carbon materials, acetylene black and polytetrafluoroethylene are thoroughly mixed evenly to form a slurry. The material is pressed into filaments under a pressure of 15 MPa to form carbon fiber filaments (1), and then dried for later use. S2. Obtain carbon fiber bundles coated with SPE coating (2): Na3Zr2Si2PO 12 The powder was continuously ball-milled for 48 hours to reduce and homogenize the particle size, so that the particle size was in the range of 50-200 nm. The ball-milled Na3Zr2Si2PO4... 12 The powder was dispersed in an isopropanol solution and further sonicated for 1–2 hours to decompose the agglomeration of nanoparticles. After preparing the PEGDA-NaClO4-SCN mixture, a specified percentage of Na3Zr2Si2PO4 was added. 12 A certain amount of Na3Zr2Si2PO was dispersed. 12 Powder, PEGDA-NaClO4-SCN-Na3Zr2Si2PO 12 The mixture was continuously stirred for 18 hours to form a uniform slurry. Then, 1% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added. The viscous slurry was then cast into a Teflon box in the order of slurry-carbon fiber filament (1) obtained in step S1-slurry and cured under ultraviolet light for 1 hour to obtain carbon fiber filament (1) coated with SPE coating (2). Multiple carbon fiber filaments (1) coated with SPE coating (2) were spirally wound to obtain carbon fiber bundle coated with SPE coating (2). S3. Printing an integrated 3D sodium-ion battery structure: Using a five-axis 3D printer, the particles after mixing conductive material (3), positive electrode active particles (4) and PLA matrix (5) are melted by a heater to obtain a hot melt. Then, the hot melt and the carbon fiber bundles coated with SPE coating (2) obtained in step S2 are co-extruded through an extrusion nozzle and printed layer by layer on a printing bed at room temperature and pressure to obtain a 3D sodium-ion battery structure. S4. Assemble the complete sodium-ion battery structure: Connect the 3D sodium-ion battery structure printed in step S3 to the aluminum current collector to realize the complete sodium-ion battery structure.

2. A sodium-ion battery according to claim 1, characterized in that: The mixing ratio of the conductive material (3) to the positive electrode active particles (4) is 4:

1.

3. A sodium-ion battery according to claim 1, characterized in that: In step S1, the temperature is set to 700℃ and the heating rate is 5℃ / min. In step S1, the mass ratio of ammonium chloride to ferric citrate is 1:

1.

4. A sodium-ion battery according to claim 1, characterized in that... The mass ratio of carbon material, acetylene black, and polytetrafluoroethylene in the slurry of step S1 is 8:1:1.

Citation Information

Patent Citations

  • Preparation method of carbon nano-fiber catalyst co-doped with iron element and nitrogen element

    CN107910564A

  • Method for manufacturing solid-state battery by using 3D printing technology

    CN114583283A

  • Positive electrode current collector solid electrolyte coating, positive electrode plate, preparation method and application

    CN115700935A